PREDICTING DIFFICULT LAPAROSCOPIC CHOLECYSTECTOMY USING CYSTIC DUCT DISSECTION TIME: A COHORT STUDY. - Kumar, Sanjay (Student's Journal of Health Research Africa, 2024)
Background: Laparoscopic cholecystectomy (LC) has emerged as the preferred surgical approach for gallstone disease due to its minimally invasive nature. However, predicting the difficulty of this procedure remains crucial for surgical planning and patient safety. To provide a safe and successful procedure, the study aims to analyze quantitative characteristics that predict difficult laparoscopic cholecystectomy (DLC) and the use of various bailout procedures. Methods: A prospective cohort study was conducted at MDB Autonomous State Medical College, Deoria, India, from July 2021 to July 2022. Fifty patients undergoing laparoscopic cholecystectomy were included based on specific criteria. Demographic, clinical, and surgical variables were collected, and statistical analyses were performed to identify predictors of difficult laparoscopic cholecystectomy (DLC). Results: The average age of the participants was 49.2 ± 6.7 years. The study revealed significant associations between urgent cholecystectomy and the use of bailout procedures (OR = 2.75, p = 0.012). Multinomial logistic regression also showed significant predictors of operative time, including BMI (β = 0.287, p = 0.008) and previous surgical history (β = -0.215, p = 0.036). A ROC curve analysis demonstrated moderate predictive accuracy (AUC = 0.78) for an operative time in predicting DLC. Conclusion: Preoperative assessment of body mass index, previous surgical history, and operative time can aid in predicting the difficulty of laparoscopic cholecystectomy. These findings underscore the importance of comprehensive evaluation and surgical planning to ensure safe and successful outcomes. Recommendations: Clinicians should consider incorporating preoperative predictors, such as BMI and surgical history, into their decision-making process for laparoscopic cholecystectomy. Future studies may further validate these predictors and explore additional factors influencing surgical difficulty.